2020
DOI: 10.1177/0022219420930814
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Algebraic Equation Solving Intervention for Students With Mathematics Learning Difficulties

Abstract: The purpose of this study was to examine the effects of algebraic equation solving intervention for sixth graders with mathematics learning difficulties (MD). A total of 48 students with MD were randomly assigned to either the algebraic equation solving intervention, Mystery Math ( n = 24) or control condition ( n = 24). The multicomponent intervention was based on the principles of explicit instruction and focused on improving conceptual and procedural knowledge of algebraic equation solving using concrete ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…As stated earlier, recent NAEP math scores are cause for concern. More specifically, only 9% of eighth graders with disabilities, and 7% of 12th graders with disabilities, performed at or above proficient levels in 2019 (NCES, 2020). Yet low performance on high–stakes math assessments is not isolated to students with disabilities.…”
Section: Performance and Classification Of Students With MDmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated earlier, recent NAEP math scores are cause for concern. More specifically, only 9% of eighth graders with disabilities, and 7% of 12th graders with disabilities, performed at or above proficient levels in 2019 (NCES, 2020). Yet low performance on high–stakes math assessments is not isolated to students with disabilities.…”
Section: Performance and Classification Of Students With MDmentioning
confidence: 99%
“…Therefore, it is necessary to provide all adolescents with instruction using effective interventions that enhance their math achievement and support a trajectory of positive outcomes. Disconcerting results from the National Assessment of Educational Progress ([NAEP], 2019, described below) suggest that many secondary students, including students with disabilities, are not proficient in core math standards National Center for Education Statistics [NCES], 2020. The NAEP reports indicate that many secondary students experience difficulties with math learning and performance.…”
mentioning
confidence: 99%
“…The data described in this analysis were collected as part of another study examining the effects of equation‐solving intervention for sixth‐grade students with mathematics learning difficulties (Namkung & Bricko, 2021). Data for the present analysis were based on 243 sixth‐grade students ( n = 108 for females, n = 135 for males) from two middle schools in one urban and one suburban school district in a midwestern state.…”
Section: Methodsmentioning
confidence: 99%
“…We extracted 20 effect sizes across studies and measures. All effect sizes reported by as well as Namkung and Bricko (2021) represented treatment to control group comparisons, and all participants in both studies had MD identifications. Bottge et al (2001) reported comparisons of treatment participants with MD to control participants without MD, as well as comparisons of treatment participants with MD to treatment participants without MD.…”
Section: Intervention Effectsmentioning
confidence: 99%